Lateral Monolayer MoSe2–WSe2 p–n Heterojunctions with Giant Built‐In Potentials. Issue 34 (21st July 2020) - Jia, Shuai; Jin, Zehua; Zhang, Jing; Yuan, Jiangtan; Chen, Weibing; Feng, Wei; Hu, Pingan; Ajayan, Pulickel M.; Lou, Jun
Abstract: 2D transition metal dichalcogenides (TMDs) have exhibited strong application potentials in new emerging electronics because of their atomic thin structure and excellent flexibility, which is out of field of tradition silicon technology. Similar to 3D p–n junctions, 2D p–n heterojunctions by laterally connecting TMDs with different majority charge carriers (electrons and holes), provide ideal platform for current rectifiers, light‐emitting diodes, diode lasers and photovoltaic devices. Here, growth and electrical studies of atomic thin high‐quality p–n heterojunctions between molybdenum diselenide (MoSe2 ) and tungsten diselenide (WSe2 ) by one‐step chemical vapor deposition method are reported. These p–n heterojunctions exhibit high built‐in potential (≈0.7 eV), resulting in large current rectification ratio without any gate control for diodes, and fast response time (≈6 ms) for self‐powered photodetectors. The simple one‐step growth and electrical studies of monolayer lateral heterojunctions open up the possibility to use TMD heterojunctions for functional devices. Abstract : Monolayer high‐quality lateral MoSe2 –WSe2 heterojunctions are successfully synthesized by a one‐step chemical vapor deposition method. The built‐in potential in MoSe2 –WSe2 heterojunction is as high as 0.72 eV, which is the highest among layered materials. The response time of heterojunction devices under zero bias is only 6 ms and much lower than that of single‐monolayer transition metal dichalcogenide‐based devices.